Factors Associated With Novice General Education Teachers' Preparedness to Work With Multilingual Learners: A Multilevel Study. (September 2021) - Deng, Qizhen; Kiramba, Lydiah Kananu; Viesca, Kara Mitchell
This study examined factors linked to novice general education teachers' perception of their preparedness to work with multilingual learners in the classroom. Using a multilevel modeling approach, we examined factors at the teacher and school levels using two AY 2015 to 2016 datasets: The National Teacher and Principal Survey from the National Center for Education Statistics and the Civil Rights Data Collection from the Office of Civil Rights. The results show that teacher perception of preparedness was positively associated with teacher education courses on working with multilingual learners, supports received during the first-year teaching, and the number of multilingual learners teachers worked within their classrooms. Similarly, the concentration of multilingual learners at the school level had a positive impact on preparedness. Overall, it appears that experiences both learning about and working with multilingual learners are positively associated with novice general education teachers' perceptions of preparedness to work with multilingual students.